Single-Stage Microsurgical Resection of Spetzler-Martin Grade III–V AVMs in Resource-Limited Settings: A Retrospective Outcome and Complication Analysis (Bangladesh Journal of Neurosurgery, 2026)
Objective: Cerebral arteriovenous malformations (AVMs) are complex vascular anomalies that often present with hemorrhage or seizures in resource-limited settings. High-grade AVMs pose significant surgical challenges, yet microsurgical resection remains the most definitive treatment with the highest obliteration rates. Aims: This study aimed to evaluate the feasibility and outcomes of single-stage microsurgical resection for high-grade cerebral AVMs. Materials and Methods: A retrospective analysis was conducted on 13 patients with Spetzler-Martin (SM) Grade III-V AVMs who underwent single-stage microsurgical resection between 2020 and 2025. Demographic information, clinical presentations, angioarchitecture details, perioperative complications, and outcomes were recorded. Post-operative complications were assessed via immediate post-operative brain CT scans, and follow-up CT angiograms at 3 months evaluated AVM resection completeness. Functional outcomes were measured using mRS scores at the last follow-up (range: 3 months to 5 years). Results: The mean patient age was 29.84 years, with a male predominance (male-to-female ratio 1.6:1) and a higher incidence of left-sided AVMs (1.6:1). The most common presenting symptoms were hemiparesis (n=7) and convulsions (n=6). Angio-architecturally, 7 patients had SM Grade III and 6 had SM Grade IV AVMs. Complete microsurgical resection was achieved in all cases (100%). Perioperative complications included cortical injury and resection bed hematoma (n=4), intraoperative brain swelling, osteomyelitis, Stevens-Johnson syndrome, and cerebral venous sinus thrombosis (each, n=1). Functional outcomes improved in 8 patients, remained unchanged in 3 patients, and 2 patients died due to perioperative complications. Conclusion: Single-stage microsurgical resection demonstrates favorable neurological outcomes despite the complexity of lesions and associated risks. However, factors traditionally considered predictive of unfavorable outcomes was not significantly correlated with poorer outcomes. Key words: Arteriovenous malformations; Functional outcome; Microsurgery, Spetzler-Martin grades; ComplicationsBang. J Neurosurgery 2024; 14(1): 13-20